1992
DOI: 10.1093/ndt/7.7.587
|View full text |Cite
|
Sign up to set email alerts
|

Familial occurrence of primary glomerulonephritis: evidence for a role of genetic factors

Abstract: Chronic glomerulonephritis was diagnosed in 23 patients born in a small valley in Northern Italy and in five additional patients with one parent or a more remote ancestor born in the same area, all belonging to three potentially related families. Eighteen patients had biopsy-proven glomerulonephritis: 11 IgA nephropathy, 3 IgM nephropathy, 2 membranoproliferative type I, and 2 mesangial proliferative glomerulonephritis with isolated C3 deposits. Ten had clinical glomerulonephritis. A community screening progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…The existence of IgM N as a distinct clinical entity has long been a matter of controversy, and HLA association studies in IgM N are scarce. Scolari et al [40, 41] reported two studies about familial IgM N; they did not find any associated HLA loci even after an extended haplotype and restriction fragment length polymorphism comparison within these families. In our study, increased frequencies of DQB1- 0401 were observed in the IgM N group as compared with the MCNS group.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of IgM N as a distinct clinical entity has long been a matter of controversy, and HLA association studies in IgM N are scarce. Scolari et al [40, 41] reported two studies about familial IgM N; they did not find any associated HLA loci even after an extended haplotype and restriction fragment length polymorphism comparison within these families. In our study, increased frequencies of DQB1- 0401 were observed in the IgM N group as compared with the MCNS group.…”
Section: Discussionmentioning
confidence: 99%
“…Four kindreds in the US were from Kentucky, one was from Connecticut and one was from Washington State. Eighteen kindreds have been reported 9,[12][13][14][15][16] ; the relationship of these kindreds to those reported previously is indicated ( Genetic analysis. We prepared genomic DNA from venous blood of kindred members as described 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies reported a higher risk of identical twins to IgAN and several cases of familial IgAN (7,8). Of note, linkage analysis of familial IgAN revealed a close association with the trait 6q22-23 (IGAN1) in this disease (9), although no proteins coded by IGAN1 have been identified.…”
mentioning
confidence: 89%